If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(-1x) + 2y = 0 Remove parenthesis around (-1x) 3x + -1 * -1x + 2y = 0 Multiply -1 * -1 3x + 1x + 2y = 0 Combine like terms: 3x + 1x = 4x 4x + 2y = 0 Solving 4x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 4x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 4x + 0 = 0 + -2y 4x = 0 + -2y Remove the zero: 4x = -2y Divide each side by '4'. x = -0.5y Simplifying x = -0.5y
| 4(a-7)+8=2(a-4) | | -6p+4p=4(1+2p)-8(2p+5) | | 4x+5x=6x | | 0.9x-0.5(5-x)=6.6 | | X(3x)=486 | | 4x+7=-30 | | -7+8=3 | | 9x+4=2x+32 | | 0.015w-1.85=1.615 | | -4(2t+8)=-8 | | -2(-7n-8)-8n=6(n-6) | | 8z+4-5z=44-5 | | 12x-2(6x-10)=1 | | g(x)=x-25x^3 | | x+36-12=42 | | 4y-12=2x | | -5(v+1)+5(1-7v)=4v+4v | | 8z+4+5z=44-5z | | -2(7n-8)-8n=6(n-6) | | -1x-7=18 | | 3(x^2+4x-1)=0 | | -20+2y=-22 | | 18+2x-12=42 | | 4(f-3)=-4 | | 2(y-1)+y=37 | | -6+14x=36 | | 10(s-6)=-129 | | 8x-24=5x+57 | | 0=x-25x^2 | | -(c-9)=-2 | | -5(5a+4)=55 | | =-x-5x-2 |